A school based community randomized trial of the effect of peer health education on primary prevention knowledge, attitude and behaviours towards HPV among adolescents (Italian Journal of Public Health, 2012)
BACKGROUND: This study in the prospect of promoting adherence to the primary and secondary preven-tion programmes will research knowledge, attitudes and behaviors of the student population attendinghigh schools regarding HPV infections and will also promote health education sessions based on peereducation.METHODS: We carried out a community randomized trial regarding HPV infection, HPV vaccination, andsexual health, of students and a peer educational intervention.To verify the effectiveness of peer educators in changing opinions and beliefs about HPV a self-com-pletion questionnaire was made and distributed pre (T1) and post (T2) peer educator intervention. Thesame questionnaires were assigned to the control group.RESULT: The sample consisted of 900 students, mean age was 16.6±1.4, having relationship 34.4%. AtT1, 64.6% of students in experimental group said that they knew HPV, 83.4% how it is transmitted and71.1% HPV vaccination, 54.7% perceived dangerousness with significant gender-related difference. AtT2 the percentages increased. At T1, 14.1% of females were vaccinated at T2 they were 17.5%. The mainfactors associated with the students’ propensity to vaccination were: having at least one sister; being infavour of vaccinations in general; knowing that the vaccine is aimed at preventing cervical cancer; andbeing aware that they could be infected by HPV.CONCLUSION: Both the HPV test and HPV vaccine need effective communication and monitoring of thespread of knowledge, especially among women identified as most in need of information and includedin the age group at risk, in wich it is crucial to encourage informed choices. This underlines the need toplan adequate educational programmes.
Keywords: HPV; Prevention; Adolescents; Peer education